“THE ROLE OF ENGLISH AS A GLOBAL LANGUAGE” (Modern education and development, 2025)
Communication is now more crucial than ever in the world that is becoming more interconnected by the day. A common language is frequently required when individuals from other nations communicate via travel, business, education, and the internet. For a variety of reasons, English has assumed this function. It is a "global language" due to its widespread